Exploring criminal capacity in terms of Executive Control Function and emotional intelligence: an investigation within the South African youth male population of Gauteng - Hasan, Maham (My University, 2021)
The law tests the criminal capacity of children as a cold cognitive component (i.e. the capability of successful mediation of emotional responsiveness to a scenario), but this does not align with current neurocognitive findings. The law assumes criminal capacity is based on adult-like Executive Control Functions (ECF) and adequate level of emotional intelligence (EI), due to a sufficiently matured brain. However, neurocognitive findings indicate variability in the rate of physiological maturation of the prefrontal cortex of adolescents, which may result in ineffective mediation of ECF and emotional responsiveness(i.e. hot cognition). This study presents the results of a quantitative study directed at an exploration of ECF and EI from two groups of boys, aged 14-17 years. A target group (N=42) of adolescents found to be in contravention of the law, and the comparison group (N=64) not in contravention with the law. ECF was measured using the Wisconsin Card Sorting Test, Tower of London and Stroop Colour Word. The EI of the participants was measured using the Schutte Emotional Intelligence Scale. Results compared developmental trends of ECF and EI between the two sample groups, as well as the difference in development between each age group within the sample groups. Findings of the empirical study confirm that youth in conflict with the law are more at risk for responsiveness guided by hot cognition due to low understanding (concept formation) and low consequential thought; exacerbated by their inability to effectively manage emotions or to utilise them in times of need
A research report submitted in partial fulfilment of the requirements of the degree of Masters in Social and Psychological Research (MASPR) at the Faculty of Humanities, University of the Witwatersrand, 2021